Inferior concha bullosa: A rare cause of nasal obstruction (Indian Journal of Case Reports, 2019)
Inferior Concha bullosa (ICB) is the presence of air cells within the inferior turbinates. Superior and middle concha bullosa are frequently encountered in the clinical practice, however, inferior concha bullosa is rarely seen. ICB is generally asymptomatic but very rarely can present with nasal obstruction. Few cases of ICB presenting with nasal obstruction have been mentioned in the literature. We, hereby report the case of a 32-year-old female presented with recurrent sinusitis and nasal blockage. Imaging revealed inferior concha bullosa with thickened turbinate. Treatment with systemic antihistaminics followed by surgery resulted in resolution of symptoms. On subsequent follow-up for one year, there were to further episodes of nasal obstruction.